2018
DOI: 10.1002/jcp.27086
|View full text |Cite
|
Sign up to set email alerts
|

An allogenic therapeutic strategy for canine spinal cord injury using mesenchymal stem cells

Abstract: This study was conducted to characterize canine bone marrow-derived mesenchymal stem cells (BMSCs); in vivo tracking in mice, and therapeutic evaluation in canine clinical paraplegia cases. Canine BMSCs were isolated, cultured, and characterized in vitro as per International Society for Cellular Therapy criteria, and successfully differentiated to chondrogenic, osteogenic, and adipogenic lineages. To demonstrate the homing property, the pGL4.51 vector that contained luciferase reporter gene was used to transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 57 publications
(80 reference statements)
0
34
0
Order By: Relevance
“…Canine SCI studies employing human UC‐MSCs (J. H. Lee, Chung, et al, ) and canine UC‐MSCs (Besalti et al, ; Lim et al, ; Park et al, ) demonstrated improved scores (Tarlov; the Basso, Beattie, Bresnahan; and Olby scores). Implantation of BM‐MSCs (Bhat et al, ; Penha et al, ) and AD‐MSCs (Park et al, ) also demonstrated improved scores and locomotion in animals. In our own clinical study in spinal cord injured dogs (n‐44), allogenic BM‐MSCs implanted in dogs at 15 days interval showed significantly improved body reflexes and recovery scores (Olby scores) as compared with those dogs managed by the conventional treatment (Bhat et al, ).…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Canine SCI studies employing human UC‐MSCs (J. H. Lee, Chung, et al, ) and canine UC‐MSCs (Besalti et al, ; Lim et al, ; Park et al, ) demonstrated improved scores (Tarlov; the Basso, Beattie, Bresnahan; and Olby scores). Implantation of BM‐MSCs (Bhat et al, ; Penha et al, ) and AD‐MSCs (Park et al, ) also demonstrated improved scores and locomotion in animals. In our own clinical study in spinal cord injured dogs (n‐44), allogenic BM‐MSCs implanted in dogs at 15 days interval showed significantly improved body reflexes and recovery scores (Olby scores) as compared with those dogs managed by the conventional treatment (Bhat et al, ).…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 99%
“…Implantation of BM‐MSCs (Bhat et al, ; Penha et al, ) and AD‐MSCs (Park et al, ) also demonstrated improved scores and locomotion in animals. In our own clinical study in spinal cord injured dogs (n‐44), allogenic BM‐MSCs implanted in dogs at 15 days interval showed significantly improved body reflexes and recovery scores (Olby scores) as compared with those dogs managed by the conventional treatment (Bhat et al, ). Besides clinical scores, significantly better histological scores (Lim et al, ; Ryu et al, ) and lower fibrosis (S. H. Lee, Kim, et al, ; Park et al, ; Park et al, ), and fewer cavitations were seen on MRI (Jung et al, ; Lee et al, , J. H. Lee, Chung, et al, ; Lim et al, ) in cell treated groups compared with control/sham groups.…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs), which have been isolated from bone marrow, umbilical cord, dental pulp, and a diversity of other tissues, have the ability of differentiating into tissue‐specific lineages . An increasing number of studies have demonstrated promising applications of MSCs in regenerative medicine and tissue engineering to repair and regenerate damaged or lost tissues due to diseases and traumatic injuries and, nonetheless, translational uses of MSCs remain inefficacious, in part due to their limited capability of migrating and homing . Thus, gaining insights into the mechanisms regulating MSC migration can provide useful information for developing novel strategies to prepare MSCs for clinical applications and improve the efficacy of MSC‐based therapies as well as evolving a better understanding of the contentious MSC biology .…”
Section: Introductionmentioning
confidence: 99%
“…Treating skin wounds with minimal scar formation is a challenge in humans as well as in veterinary medicine (Jackson, Nesti, & Tuan, 2012). One possible solution is cytotherapy or transplantation of mesenchymal stem cells (MSCs; Bhat et al, 2018). Over the past decade, stem cell‐based regenerative therapy is gaining popularity due to their capacity to renew themselves through mitotic cell division and differentiation into specialized cell types of diverse range (Ilic & Polak, 2011).…”
Section: Introductionmentioning
confidence: 99%